Effect of Rubberized Bitumen Blending Methods on Permanent Deformation of SMA Rubberized Asphalt Mixtures - Katman H.Y.; Ibrahim M.R.; Karim M.R.; Koting S.; Mashaan N.S. (Hindawi Limited, 2023)
Asphalt; Binders; Bins; Blending; Creep; Creep testing; Deformation; Mastic asphalt; Materials testing; Materials testing apparatus; Mixtures; Shotcreting; Creep behaviour; Deformation Characteristics; Dynamic creeps; Permanent deformations; Rubberized asphalt; Stone mastic asphalts; Terminal blends; Test condition; Asphalt mixtures